MỘT SỐ KẾT QUẢ NGHIÊN CỨU MỚI RANH GIỚI MẶN NƯỚC DƯỚI ĐẤT VÙNG ĐỒNG BẰNG NAM BỘ - Bình, Bùi Tiến (Vietnam Journal of Earth Sciences, 2011)
New studied results on saline interfaces in Mekong delta’s aquifersGeophysical logging and vertical electrical sounding methods play important roles in the study of groundwater salinity boundaries in Mekong delta (MD). There are now over 13,000 electrical sounding points and nearly 800 geophysical logging boreholes that have been done in different research project areas in the whole MD with the mainobjective being to determine the distribution of the saline boundaries in the herein aquifers.Geoelectrical standards to define the saline boundaries in the aquifers were determined from the correlationbetween the value of resistivity of underground environment and the total mineralization of underground water. However,recent studies on the aspects of geology, hydrogeology, geophysics, etc. at the medium and large map scales in different areas of the MD indicated that the current standards are no longer appropriate.The article also gives some examples in the recent studies conducted in the MD region to compare with the saltwater boundaries that were determined in an overall study project at map scale of 1:500.000 several years ago and explains about the necessity to rebuild newly standards. Since then, the proposing a new model of saltwater lines in a larger scale, which is consistent with the objectives of the investigation and planning of groundwater resources in the MDregion in the coming years is essentially.